Reduction of persistent photoconductivity in a few-layer MoS2 field-effect transistor by graphene oxide functionalization. Issue 28 (1st March 2016) - Rathi, Neha; Rathi, Servin; Lee, Inyeal; Wang, Jianwei; Kang, Moonshik; Lim, Dongsuk; Khan, Muhammad Atif; Lee, Yoontae; Kim, Gil-Ho
Abstract : Reduction in persistent photoconductivity by functionalizing MoS2 FET with graphene oxide. Abstract : We functionalized two-dimensional few-layer MoS2 based FET with graphene oxide (GO) in order to improve its persistent photoconductivity and photoresponse time. Both pristine and GO functionalized devices show n-type semiconductor behavior with high on/off ratio exceeding ∼10 5 . The photoresponse of the GO–MoS2 hybrid device shows almost complete recovery from persistent photoconductivity and a substantial decrease in response time from ∼15 s in the pristine MoS2 device to ∼1 s in the GO–MoS2 device. The reasons behind this improvement have been explored and discussed on the basis of electrostatic and photo interaction between GO and MoS2 . As GO is a strong candidate for various sensing applications, therefore this intelligent hybrid system, where GO interacts electrostatically with the underlying MoS2 channel, has tremendous potential to add more functionalities to a pristine MoS2 device for realizing various smart nanoscale FET-based biochemical and gas sensors for myriad applications.